Cervical spondylotic radiculopathy: the role of conservative management - See, Lei Peng; Zakaria@Mohamad, Zamzuri; Karupiah, Rajandra Kumar; Perwira, Marzuki (Kulliyyah of Medicine, International Islamic University Malaysia, 2018)
BACKGROUND Cervical spondylotic radiculopathy is common and most patients experiencing an acute episode of unilateral radiculopathy without major motor decit and no evidence of cord compression can be managed by non-operative measures.